A management work to introduce a jointly-operated bus system by multiple companies: Workplace mobility management based on diverse types of communication in a transportation poor area - SAKAI, Hiromu; MURAO, Toshimichi; FUJII, Satoshi (INFRASTRUCTURE PLANNING REVIEW, 2008)
Organizational behavior change to introduce a bus system jointly-operated by multiple companies is an effective workplace mobility management measure especiallyin a transportation poor area. However implementation of the measure is not always easy and therefore it always requires efforts of the mobility management conductor. Therefore, key points for the successful introduction of such bus impliedby the actual experience would be helpful for implementation of workplace mobility management in the other places. With this recognition, we reported a process of introduction process of a jointlyoperated bus system by multiple companies inindustrial park neighboring area, its consequences, and key points of the success of the introduction.